Nurses’ Experiences with Disclosure of Patient Safety Incidents: A Qualitative Study - Kim Y; Lee H (Dove Medical Press, 2020)
Yujeong Kim,1 Haeyoung Lee2 1College of Nursing, Research Institute of Nursing Science, Kyungpook National University, Daegu 41944, Republic of Korea; 2Red Cross College of Nursing, Chung-Ang University, Seoul 06974, Republic of KoreaCorrespondence: Haeyoung Lee 84 Heukseok-ro, Dongjak-gu, Seoul 06974, Republic of KoreaTel +82-10-3117-6381Email im0202@cau.ac.krBackground: Patient safety incidents trigger conflict between healthcare providers and patients. Patients and families want to hear detailed explanations and apologies from medical staff, but nurses may face difficulties with disclosure of patient safety incidents.Purpose: To identify nurses’ experiences with disclosure of patient safety incidents.Methods: Data were collected through in-depth interviews with nine clinical and five head nurses and were analyzed using Colaizzi’s phenomenological method.Findings: After formulating 18 themes representing nurses’ experiences with disclosure of patient safety incidents, we clustered them into four theme clusters: “mixed responses from patients and families,” “caught in a swirl of negative emotions,” “facing the reality that hinders disclosure,” and “waiting for a breakthrough that would enable disclosure”.Conclusion: Policies, systems, and culture that help both patients and healthcare professionals should be developed.Keywords: disclosure, medical errors, nurses, patient safety, qualitative research